Current perspectives on neonatal hypoglycemia, its management, and cerebral injury risk - Chandran S; Rajadurai VS; Abdul Haium AA; Hussain K (Dove Medical Press, 2015)
Suresh Chandran,1–4 Victor Samuel Rajadurai,1–3 Abdul Alim Abdul Haium,1–3 Khalid Hussain5,6 1Department of Neonatology, KK Women’s and Children’s Hospital, Singapore; 2Duke-NUS Graduate School of Medicine, Singapore; 3Yong Loo Lin School of Medicine, National University of Singapore, Singapore; 4Lee Kong Chian School of Medicine, Nanyang Technological University, Singapore; 5Department of Paediatric Endocrinology, Great Ormond Street Hospital for Children, NHS Foundation Trust, London, 6The Institute of Child Health, University College London, London, UK Abstract: Glucose is an essential substrate for mammalian cells; in particular, the brain needs glucose continuously as a primary source of energy. Hypoglycemia is the most common biochemical finding in the neonatal period. However, despite the common occurrence, there is still controversy on the definition of hypoglycemia in the newborn period. This has led to the development of guidelines designed to identify infants “at-risk” and the implementation of an “operational threshold” for physicians to consider intervention. In healthy term infants, the optimal hormonal and metabolic adaptations during the immediate neonatal period ensure an adequate energy substrate for the vital organs, whereas the abnormal glucose homeostasis observed in preterm and growth-retarded infants is multifactorial in origin. For these high-risk infants, it is important to identify, screen, and prevent significant hypoglycemia. Detailed investigations are warranted in infants with severe and persistent hypoglycemia. Neonatal hypoglycemia is a major cause of brain injury. The speculated mechanisms of cellular injury include excitatory neurotoxins active at N-methyl-D-aspartate receptors, increased mitochondrial free radical generation with initiation of apoptosis and altered cerebral energetic characteristics. This hypoglycemic brain injury predominantly affects parieto-occipital regions causing cognitive, sensory, psychomotor, and behavioral deficits in children. This state of the art review article covers the fetal–neonatal metabolic adaptation, glucose homeostasis in normal and abnormal conditions, management strategies, and late neurological sequelae of hypoglycemia. Keywords: hyperinsulinism, hypoglycemic brain injury